Clinicopathological Characteristics of Invasive Breast Carcinoma on PDL-1 Immunohistochemical Expression in H. Adam Malik Hospital Medan - Daniel Kristian Prawira Lesmana; Denny Rifsal Siregar; Dedy Hermansyah (Sumatera Medical Journal, 2023)
Background: Immune biologic markers that can predict clinical response to anti-PD-1/PD-L1 therapy are needed to identify and validate tumor immunotherapy studies. High PD-L1 expression is associated with increased clinical response in patients with various types of cancer treated with inhibitors of the PD-1/PD-L1 pathway. Objective: The researcher wanted to see the clinicopathological characteristics of invasive breast carcinoma according to the immunohistochemical expression of PD-L1. Methods: This study is a descriptive study with a cross-sectional, retrospective approach by looking at secondary data from the medical records of the Department of Surgery, Haji Adam Malik Hospital from January 1, 2019, to December 31, 2021. Results: Immunohistochemical expression of PD- L1 was positive in 76.6% of invasive breast carcinomas and negative in 23.3% of invasive breast carcinomas. Immunohistochemical expression of PD-L1 was positive in non-specific IBCs that predominated in every molecular subgroup of breast carcinoma. Conclusion: Tumours can show positive or negative PD-L1 expression through several biological processes with different functional significance, namely the genetic mechanism of constitutive or oncogene-induced PD-L1 expression, PD-L1 expression induced in T cells, and absence of PD-L1 expression. Due to the absence of T cells and genetic events that block the expression of PD-L1 despite T cell infiltration.